The Effect of Providing Extrinsic and Intrinsic Motivation on Student Learning Difficulties - Manda, Darman (Universitas Sulawesi Barat, 2023)
This study aims to understand the combined effect of extrinsic and intrinsic motivation on students' learning difficulties at the junior secondary school level. This research uses a qualitative approach with a case study method. The informants consisted of 10 people, including students with learning difficulties, subject teachers, guidance and counselling (BK) teachers, and parents. Data were collected through in-depth interviews and participant observation in the classroom to see the implementation of motivational strategies in the learning process. Interviews were conducted to obtain informants' perspectives on motivation and learning difficulties. Data were analysed using thematic analysis method and data triangulation to ensure the validity of the findings. The results show that the combination of extrinsic motivation, such as rewards and praise, with intrinsic motivation, such as curiosity and personal interest, can have a significant synergistic effect in reducing students' learning difficulties. This research is expected to contribute to the literature on motivation in educational contexts and provide practical guidance for educators in developing effective motivational strategies to support students with learning difficulties.